Female predominance and socio-demographic inequalities in global near vision loss burden: projected trends and disparities from 1990 to 2035 - Tang, Guodong; Li, Jing; Gong, Xiaoqi; Yu, Han; Jiang, Man; Han, Yibo; Wang, Dongfang; Liu, Yuxi; Song, Jike; Bi, Hongsheng (Frontiers in Public Health, 2025)
BackgroundNear vision loss (NVL), a hallmark of aging populations, imposes a growing global health burden, exacerbated by demographic shifts and socioeconomic disparities. Despite its profound impact on productivity and quality of life, comprehensive analyses that integrate aging, socioeconomic development, and sex-specific disparities remain limited.MethodsUsing the Global Burden of Disease (GBD) 2021 dataset spanning 204 countries and territories (1990–2021), we evaluated the NVL burden through prevalence, disability-adjusted life years (DALYs), and sociodemographic index (SDI). Advanced methodologies included decomposition analysis to disentangle demographic and epidemiological drivers, Bayesian age-period-cohort (BAPC) modeling for projections, and frontier analysis to quantify SDI-linked inequities. Gender-stratified and age-specific trends were analyzed using joinpoint regression analysis.ResultsGlobal NVL prevalence surged from 428 million to 1.155 billion cases (1990–2021). Females exhibited a higher age-standardized prevalence (16,588 vs. 14,718 per 100,000 in 2021). South Asia had the highest burden (age-standardized DALYs: 208.0), whereas the Gulf Cooperation Council reported the lowest (93.8). Socioeconomic inequities widened: The DALY gap between high- and low-SDI regions expanded from 10.19 to 31.96. Population growth (65.3%) and epidemiological shifts (39.2%) drove DALY increases, offset marginally by aging (−4.4%).ConclusionNVL burden escalated disproportionately in low-SDI regions and among females, fueled by population growth and systemic healthcare gaps. Aging, while a minor contributor globally, critically affects the high-income Asia-Pacific region. Policymakers must prioritize sex-sensitive refractive care programs, expand optical subsidies in underserved areas, and address digital near-work hazards to mitigate the premature onset of NVL.